1998
DOI: 10.1139/b98-110
|View full text |Cite
|
Sign up to set email alerts
|

The genus Uncinocarpus (Onygenaceae) and its synonym Brunneospora: new concepts, combinations and connections to anamorphs in Chrysosporium, and further evidence of relationship with Coccidioides immitis

Abstract: The genus Uncinocarpus (Onygenales, Onygenaceae) is emended to include keratinophilic fungi with discrete, globose gymnothecial ascomata without differentiated ascomatal hyphae and bearing uncinate, helical, or no appendages; oblate, punctate ascospores sometimes with irregular reticulations; bulbous initials, and Malbranchea or Chrysosporium anamorphs. The new combination Uncinocarpus orissi is proposed for Pseudoarachniotus orissi; Gymnoascus arxii is shown to be a synonym. New records show that the fungus h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…Aleurioconidia were club shaped to broadly obovoid (egg shaped), were slightly warty, and measured 5 to 7 m long and 3 to 4 m wide; arthroconidia measured 7 to 11 m long and 2 to 3 m wide. The identification was confirmed by mating the case isolate with reference strains of Uncinocarpus orissi, which was identified previously as the teleomorph of C. zonatum (12). It was determined as a plus mating type based on its formation of ascomata and ascospores when paired with a minus mating type strain (UAMH 8936).…”
Section: Case Reportmentioning
confidence: 89%
See 2 more Smart Citations
“…Aleurioconidia were club shaped to broadly obovoid (egg shaped), were slightly warty, and measured 5 to 7 m long and 3 to 4 m wide; arthroconidia measured 7 to 11 m long and 2 to 3 m wide. The identification was confirmed by mating the case isolate with reference strains of Uncinocarpus orissi, which was identified previously as the teleomorph of C. zonatum (12). It was determined as a plus mating type based on its formation of ascomata and ascospores when paired with a minus mating type strain (UAMH 8936).…”
Section: Case Reportmentioning
confidence: 89%
“…C. zonatum is recognized by its fast growth at 37°C and by colonies that darken to buff. First described in 1989 in Kuwait, this species is now known to occur in North America, Europe, Asia, and the Middle East (12). Mating studies revealed that the species is the anamorph of an ascomycete that has been named U. orissi (Onygenaceae) (12); however, the placement of the teleomorph in the genus Uncinocarpus was disputed in a later study (14).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Their closest relative for which a genome sequence is currently published, determined by both phylogenetic analysis and morphology, is Uncinocarpus reesii (Onygenaceae), a keratinophilic saprotroph (6,7). Whereas U. reesii has a known sexual life cycle (7,8), the sexual cycle of Coccidioides remains undescribed. No other dimorphic pathogens of humans have been described in the Onygenaceae family (7,9,10).…”
Section: Mycology and Population Structurementioning
confidence: 99%
“…Whereas U. reesii has a known sexual life cycle (7,8), the sexual cycle of Coccidioides remains undescribed. No other dimorphic pathogens of humans have been described in the Onygenaceae family (7,9,10). The Onygenales order, however, contains other dimorphic pathogens, such as Paracoccidioides brasiliensis, Ajellomyces (Histoplasma) capsulatus, and Ajellomyces (Blastomyces) dermatitidis (10,11).…”
Section: Mycology and Population Structurementioning
confidence: 99%